Import Determinants and Potential Markets of Pakistan: an Application of PPML Gravity Model - Wani, Suadat Hussain; Mir, M. Afzal (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
The present study examines import determinants of Pakistan with the top 28 trade partners from 2002 to 2018. To achieve this objective, the augmented gravity model of trade has been applied by incorporating both time-variant and time-invariant variables. In addition, the analysis quantifies the impact of free trade agreements (FTA) signed by Pakistan with China and other trade partners. The results show that along with income and distance, FTA, common language, and common border plays an essential role in imports of Pakistan with its main trade partners. In addition to identifying trade determinants, the impact of adherence to a particular trade agreement was also examined. The results indicate that FTA signed by Pakistan with China and other trade partners has created trade opportunities for participating countries, highlighting the importance of trade liberalization for the long-run development of the country.